Gambaran Pelayanan Keperawatan Spiritual di Rumah Sakit - Amal, A.Adriana; Hidayah, Nur; Rauf, Syamsiah (Jurusan Keperawatan Poltekkes Kemenkes Denpasar, 2024)
Spirituality is one of the essential domains in nursing care, encompassing bio-psycho-social-spiritual aspects. The implementation of spiritual nursing care can support the patient healing process but is often overlooked. This study aims to evaluate the implementation of spiritual nursing care in hospital. This research is a descriptive quantitative study involving 85 nurses selected through cluster random sampling. Data were collected using a questionnaire instrument to measure spiritual nursing care at the hospital, namely the Nurse Spiritual Care Therapeutic tool. The collected data were then analyzed descriptively to provide an overview of the implementation of spiritual nursing care at Ibnu Sina Hospital Makassar. The results showed that 49,4% of respondents reported that spiritual nursing care had been implemented well. The support and counseling domain had the highest mean score of 3,56, followed by the assessment and implementation domain at 3,51. The spiritual referral domain had a mean score of 3.31, while the communication domain was the lowest, with a mean score of 3,28. Although spiritual nursing care at Ibnu Sina Hospital Makassar has been implemented, it is not yet optimal. The support and counseling domain performed well, but communication requires further improvement to enhance the overall success of spiritual nursing care. Training and improving nurses' communication competencies are crucial for providing more effective and comprehensive care to patients.